Crescimento, fotossíntese e nutrição de genótipos de Coffea canephora enxertados em porta-enxertos tolerantes a estresses - Brinate, Sebastião Vinícius Batista (2018)
The success of the coffee activity is a consequence of the management of crop implantation, being, of great importance in the process, a use of productive and tolerant plants and situations of stress that lead to an accommodation of these plants. Therefor